MATERNAL AND FETAL OUTCOMES IN WOMEN RECEIVING URSODEOXYCHOLEIC ACID (UDCA) AS TREATMENT FOR INTRAHEPATIC CHOLESTASIS OF PREGNANCY (IHCP), A SINGLE CENTER EXPERIENCE: ARE WE DOING ENOUGH? - QURESHI, SR; ALVI, AH; CHACHAR, AZK; SOHAIB, M; ALI, S; ABDULLAH, M (Biological and Clinical Sciences Research Journal, 2023)
Intrahepatic cholestasis of pregnancy (IHCP) is a common type of hormonally driven cholestasis in the late second or early third trimester of pregnancy. It’s a reversible condition and has a genetic predisposition. This study aimed to analyze the maternal and fetal outcomes of women being treated with Ursodeoxycholic acid (UDCA) for IHCP. Seventy-five pregnant women with IHCP were included in this observational cross-sectional study, with a study duration of one year. SPSS software version 24.0 was used to analyze the data collected by the investigating officer. Laboratory and clinical parameters were assessed at presentation and after treatment. Results showed that 92% of pregnant women with IHCP had significantly raised serum bile acid levels. However, UDCA treatment caused complete resolution of itching in 57.7% of patients, reduced to mild in 40.4%, and moderate itching in 1.9% of patients. Mean Alkaline Phosphatase and ALT levels significantly decreased after UDCA treatment, with p-values of 0.001 and 0.004, respectively. The dose of UDCA required ranged from 10-25 mg/kg/day. A positive family history of IHCP was found in 36.5% of patients, while 33% had a history of IHCP in previous pregnancies, and 16% had twin pregnancies. The incidence of early delivery was high at 98%, with a mean gestational age of 36.4 weeks. Among these early deliveries, 8% had vaginal delivery, and 92% had C-sections. The indications of delivery were intractable itching and no improvement in LFTS in 15%, PROM and fetal distress in 21%, failed induction in 31%, previous cesarean in 23%, and other reasons in 10%. The study found that 99% of babies had good APGAR scores and no morbidity. However, 1% mortality was reported due to severe IHCP in the mother. In conclusion, UDCA treatment significantly improved physical and laboratory parameters and effectively treated IHCP. Early delivery had better maternal and fetal outcomes.